PENENTUAN PREMI MURNI DI KABUPATEN KEPAHIANG PROVINSI BENGKULU DENGAN MEMPERHITUNGKAN PELUANG KEJADIAN GEMPA BUMI DAN RASIO KERUSAKAN BANGUNAN - Tiara Yulita; Chaterine Theresia Lubis; Agus Sofian Eka Hidayat (Statistics Study Programme, Department of Mathematics, Faculty of Mathematics and Natural Sciences, University of Pattimura, 2023)
Indonesia is a country that is very vulnerable to earthquakes, one of which is in Bengkulu Province, especially Kepahiang Regency. To deal with risks or losses caused by earthquakes, insurance can be purchased. Therefore, in this study, earthquake insurance premiums will be determined by taking into account the probability of an earthquake occurring and the ratio of damage to buildings in Kepahiang Regency. The PSHA (Probabilistic Seismic Hazard Analysis) method is used to determine the probability of an earthquake occurring. In the PSHA process, earthquake data will be collected and analyzed to identify earthquake sources, characterize earthquake sources, and calculate earthquake hazard (the probability of an earthquake). Damage data on buildings will be processed to obtain a ratio of building damage. After that, a pure premium will be obtained, by multiplying the EADR (Expected Annual Damage Ratio) value with the sum insured of the building, where EADR is the estimated level of annual damage due to earthquakes in an area